First multiply 3 and the 1
Then simplify b^2-4b+3=0
Then divide both numbers by 3 (b-3/3)(b-1/3)=0
If it doesn’t go in even like the second term then bring it before the B
Then equal both terms to 0 and solve
1/18 can't be simplified because 1 cant be simplified. What ever happens to one side of the equation happens to the other, so nothing can happen to the 1 so nothing can happen to the 18
It cant be simplified
Answer:
(x + 1)² + (y + 3)² = 16
Step-by-step explanation:
The equation of a circle in standard form is
(x - h)² + (y - k)² = r²
where (h, k) are the coordinates of the centre and r is the radius
Given
x² + y² + 2x + 6y - 6 = 0
Collect the x and y terms together and add 6 to both sides
x² + 2x + y² + 6y = 6
To complete the square
add ( half the coefficient of the x/ y terms )² to both sides
x² + 2(1)x + 1 + y² + 2(3)y + 9 = 6 + 1 + 9
(x + 1)² + (y + 3)² = 16
with centre = (- 1, - 3) and r =
= 4